A framework designation for the assessment of urban ecological risks. Issue 5 (4th July 2018) - Tang, Lina; Wang, Lin; Li, Qianyu; Zhao, Jingzhu
ABSTRACT: Urban ecological risks stemming from urbanization are increasing and limiting the capability of China to effectuate sustainable urban development. Therefore, addressing urban ecological risks is an urgent need. Numerous factors are involved in urban ecological risks, including air, water, and soil. Additionally, risk sources and risk receptors are complex and diverse. In this study, urban ecological risks are defined as adverse effects and possibility of impacts on urban ecosystem services resulting from urbanization. Urbanization is recognized as the risk source, and the urban ecosystem is considered the risk receptor. Based on this understanding, the components of urban ecological risks are defined, and the relationships between the components of urban ecological risks are illuminated by establishing an indicator system. Based on previous studies on urban ecological risks, an explicit framework for identification, assessment, and management of urban ecological risks is proposed. For purposes of identification, there are three types of risk sources: population growth, industrial development, and the expansion of built land. Stressors include the accumulation of contaminants, consumption of resources, and occupation of space. Assessment endpoints are divided into provisioning, regulating, cultural, and supporting services. In response to urban ecological risks having multiple stressors and multiple assessment endpoints, we assessed risks both with a single stressor/single endpoint and comprehensive ecological risks. In our framework, the physical or material assessment of ecosystem services is adopted as the core method for the analysis of urban ecological risk, because it is believed that the analysis of urban ecological risk should be based on the physical or material assessment of ecosystem services instead of the value assessment of ecosystem services. The results of the single value assessment of urban ecosystem services will cause the deviation from the purpose of urban ecosystem services assessment. The purpose of urban ecosystem services assessment is to maintain and/or improve the capability of urban ecosystems of providing physical or material services, and further to reduce or avoid the occurrence risks of unsustainable cities. Additionally, a multi-level characterization method was adopted for the results of urban ecological risk assessment. In this study, we established a platform to manage urban ecological risks based on landscape ecology and environmental internet of things technologies, and to effectuate online urban ecological risk identification, assessment, and management via this platform.